Long‐term quality of life in octogenarians and nonagenarians with nonvalvular atrial fibrillation following WATCHMAN™ device implantation. Issue 6 (12th December 2018) - Ramos Tuarez, Fergie J.; Pino, Jesus E.; Alrifai, Abdulah; Kabach, Mohamad; Donath, Elie; Saona, Jorge; Chavez, Julio Grajeda; Diaz, Ximena Torres; Jimenez, Marcelo; Chait, Robert
Abstract: Objectives: To assess the impact of WATCHMAN™ on quality of life (QoL) in octogenarians and nonagenarians. Background: QoL after WATCHMAN™ device in the elderly remains unknown. Methods: This is a prospective and retrospective cohort study of patients that underwent WATCHMAN™ implantation in a tertiary cardiovascular center from April 1, 2015 to September 27, 2017. The primary outcome was a prospective assessment of QoL via the SF‐12v2 Health Survey (SF‐12v2) in those aged ≥80 and ≥90 years. Secondary outcomes include major bleeding, stroke, vascular complications, pericardial effusion, device related thrombus (DRT), prolonged length of stay (LOS), acute kidney injury (AKI), and recurrent hospitalizations. Results: This cohort of 151 patients included 48/151 (32%) females with a mean age of 80 ± 7.7 years. Mean CHA2 DS2 ‐VASc was 4.38 ± 1.36 and mean HAS‐BLED was 3.27 ± 1.17. Octogenarians 65/81(80%) and nonagenarians 16/81(20%) comprised 81/151(54%) of patients (mean age 86 ± 4.3 years) from which 36/65 (55%) octogenarians and 10/16 (63%) nonagenarians completed SF‐12v2 evaluation at 22 ± 10 and 30 ± 10‐months. Octogenarians demonstrated enhanced physical component scores (PCS), and nonagenarians equal PCS versus the age‐adjusted norm (45.43 ± 9.84 versus 38.68 ± 11.04, P  = 0.0003, and 41.26 ± 12.36 versus 38.68 ± 11.04, P  = 0.6463, respectively). The mental component scores (MCS) of octogenarians and nonagenarians remained comparable (51.80 ± 9.56 and 48.97 ± 9.92 versus 50.06 ± 10.94, respectively, P  = 0.4659). No stroke, vascular complications, pericardial effusions, or readmissions related to WATCHMAN™ occurred. No difference among patients <80, ≥80, and ≥90 years was found in major bleeding events, DRT, prolonged LOS, or AKI ( P  = 0.0569, 0.116, 0.498, and 0.795, respectively). Conclusions: Octogenarians and nonagenarians experience favorable long‐term QoL after WATCHMAN™, with acceptable bleeding risk and low incidence of procedure‐related complications.